The Tower of Babel: Practical notes on horizontal property regulations in mixed-use projects - Chan, Alfredo (2023)
The biblical story of the Tower of Babel, in addition to teaching us the importance of communication, can teach us how important it is to establish certain basic rules when sharing a space with other people. These basic rules can be seen embodied, contemporarily, in the rules of condominiums.In the article, the authors explore the nature of these regulations, their basic contents and the functions they perform. Mainly, the bylaws serve to reduce transaction costs between the parties involved, so that they can reach agreements that allow coexistence in a scenario of own and common property.